Uma análise de plataformas de streaming e as possibilidades para um guia de programação na TV 3.0 - Montezano, Cristiane Turnes; Pernisa Júnior, Carlos; Moreno, Marcelo F. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
This study explores the presence and role of the Electronic Program Guide (EPG) in streaming platforms, aiming to understand how the next-generation television, known as TV 3.0, might adapt to content organization. With the advent of TV 3.0, new requirements emerge, such as app-driven navigation and the integration of OTA (over-the-air) and OTT (over-the-top) content, necessitating significant transformations in the viewer experience. We believe that streaming platforms offer an initial model that can guide these changes, bringing the TV 3.0 interface closer to the established format of current streaming services. However, one of the greatest challenges will be balancing digital complexity with the need to maintain the simplicity and fluidity that viewers are accustomed to, ensuring that the new TV retains its identity. In this context, the EPG emerges as a crucial tool to facilitate viewers’ adaptation and understanding of this new form of television interaction. The research was conducted through an exploratory bibliographic analysis, which included a detailed study of the interfaces of three streaming platforms: Globoplay, RTVEplay, and Pluto TV. These platforms combine on-demand content with live and linear broadcasts. This article is part of a broader study on the potential interfaces for the TV of the future, with a focus on content organization on screen and viewer interaction.